Herpes Simplex Mastitis in an Adolescent Woman: Clinical and Ultrasound Features - Seung Kwan Kim; Bo Kyoung Seo; Hwa Eun Oh (대한영상의학회지, 2020)
Herpetic mastitis is extremely rare, and its imaging findings remain unclear. We report a case of herpes simplex mastitis in an adolescent woman and describe the clinical and ultrasound features. The patient showed unilateral nipple and areolar skin thickening and axillary lymphadenopathy on B-mode ultrasonography. Doppler ultrasonography revealed multiple linear and branching blood flows in the areolar area. The lesion was verified as herpes simplex mastitis via a skin biopsy. This report shows that the radiologic features of herpes simplex mastitis may be similar to those of Paget’s disease because of localized nipple and areolar skin thickening and increased vascularity.